Migratory pathways, stopover zones and wintering destinations of Western European Nightjars Caprimulgus europaeus. (14th March 2017) - Evens, Ruben; Conway, Greg J.; Henderson, Ian G.; Cresswell, Brian; Jiguet, Frédéric; Moussy, Caroline; Sénécal, Didier; Witters, Nele; Beenaerts, Natalie; Artois, Tom
Abstract : Little is known about the wintering distribution of the European Nightjar Caprimulgus europaeus . We combined geolocator and GPS‐logger data from different sites in Western Europe to analyse migration routes and migration timing of this trans‐equatorial migrant. Nightjars followed a loop migration route during which they cross two ecological barriers, and converged near common stopover zones in Northern, Central and Western Africa, where they stayed for 2–3 weeks. Nightjars used the same stopover sites as several other European migrants, relying on small and discrete wintering areas within the Democratic Republic of Congo. This confirms the importance of these specific zones and highlights the vulnerability of Western European populations to habitat loss in their non‐breeding areas.